Effects of intracuff and intravenous lignocaine on recovery from anaesthesia after thyroid surgery. A single-centre randomised double-blind placebo-controlled trial (The IOLANT study) - Sergey M. Efremov; Alexey Y. Kulikov; Valeria P. Govorushkina; Daniil D. Sidorov; Alexey A. Ladutko; Oleg V. Kuleshov (Indian Journal of Anaesthesia)
Background and Aims: Despite evidence that local intracuff alkalinised lignocaine may reduce the incidence of exaggerated laryngeal reflexes after thyroid surgery, its effects on the quality of recovery (QoR) from anaesthesia remain unknown. This study aimed to test if local intracuff alkalinised lignocaine improves the QoR from anaesthesia after thyroid surgery compared to placebo. Methods: Patients over 45 years old scheduled for thyroid surgery with electromyographic monitoring under general anaesthesia were enroled in a randomised, single-centre, double-blind, placebo-controlled trial. They were randomised into three groups (1:1:1 ratio): intravenous lignocaine (IVL), topical and intracuff lignocaine (TL), and placebo. The sample size was initially set at 231, but the study was terminated early after an interim analysis of 110 patients showed no significant difference between groups. The primary outcome was the QoR-40 score 24 hours post-surgery. Secondary outcomes included rates of arterial hypotension, coughing during emergence, bispectral index (BIS) values, and electromyographic monitoring characteristics. Results: An interim analysis after 110 patients showed mean QoR-40 scores of 185 (standard deviation(SD): 11.4) (placebo), 186.1 (SD: 13.6) (IVL), and 185.1 (SD: 14.3) (TL) (P = 0.662). Mean differences were 1.1 (IVL vs placebo, 95%CI: −5.03, 7.15, z = 0.347) and 0.1 (TL vs placebo, 95%CI: −6.02, 6.23, z = 0.035). The study was stopped due to lack of effectiveness as the superiority of IVL and TL was not demonstrated. No differences were found in secondary outcomes. Conclusion: Neither IVL nor TL improved the QoR from anaesthesia and did not affect electromyographic monitoring in low-risk thyroid surgery.